Pro Kontra Nikah Ulang Pasca Nikah Siri Dalam Pandangan Kepala KUA Di Kabupaten Temanggung - Yeni Mafiah; Siti Zumrotun (Indonesia, 2023)
This research was motivated by the existence of several siri marriage couples who registered their marriages with the KUA. There was one siri marriage couple that the author managed to interview, and found data that the couple remarried at the KUA after they had previously conducted a siri marriage first. The purpose of writing this article is to examine the pros and cons in the view of the Head of the KUA in Temanggung Regency regarding remarriage after siri marriage. This research is field research or Field Research, using a qualitative descriptive approach, in which the author conducts observations and interviews directly with the Head of the KUA in Temanggung Regency. The result of the research is that there are differences of opinion about remarriage after siri marriage in the view of the Head of the KUA in Temanggung Regency. Some argue that there is no problem with the implementation of remarriage after siri marriage on the grounds that basically siri marriage is a marriage that is not valid according to the state so that the perpetrator of siri marriage is considered never married as long as the marriage has not been recorded by an authorised official. And there are those who disagree with the existence of remarriage, because there is another alternative, namely isbat nikah. Meanwhile, in the context of tajdīdu'n-nikāḥ (renewing marriage) according to most scholars, the law is permissible. This research is expected to open the insights of all parties that in addition to remarriage, isbat nikah also has an important role in alternative solutions to the problem of nikah siri.